2003
DOI: 10.4049/jimmunol.171.2.576
|View full text |Cite
|
Sign up to set email alerts
|

Blocking 4-1BB/4-1BB Ligand Interactions Prevents Herpetic Stromal Keratitis

Abstract: Herpetic stromal keratitis (HSK) is a chronic inflammatory process in corneal stroma that results from recurrent HSV type 1 infection. We used the murine model of HSK to demonstrate the importance of the interaction between an inducible T cell costimulatory receptor, 4-1BB, and its ligand, 4-1BB ligand (4-1BBL), in the development of this disease. In BALB/c mice, HSK ordinarily induced by infection with the RE strain of herpes was prevented by blocking 4-1BB/4-1BBL interaction, either by deleting 4-1BB (in mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 29 publications
2
44
1
Order By: Relevance
“…In in vivo viral infection models, 4-1BB costimulation has been shown to affect mainly the antiviral CD8 ϩ T cell response (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Interestingly, studies by Bertram et al (22,23) have revealed a specific role for 4-1BB costimulation in the maintenance of memory CD8…”
Section: Ostimulatory Signals Provide Secondary Signals To T Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…In in vivo viral infection models, 4-1BB costimulation has been shown to affect mainly the antiviral CD8 ϩ T cell response (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Interestingly, studies by Bertram et al (22,23) have revealed a specific role for 4-1BB costimulation in the maintenance of memory CD8…”
Section: Ostimulatory Signals Provide Secondary Signals To T Cells mentioning
confidence: 99%
“…The kinetics of 4-1BB expression during infection with HSV is also transient, although the peak of expression differs with the route of infection (27,29). We sought to analyze the expression of 4-1BB on virusspecific CD8…”
Section: T Cells During Mhv-68 Infection 4-1bb Expression On Cd8mentioning
confidence: 99%
“…In graft-vs-host disease models, 4-1BB/4-1BBL can play an equivalent role in MHC-I-or MHC-II-restricted disease (28), although the same is not true for OX40 (29). Furthermore, 4-1BB is required for herpes simplex 1-mediated keratinitis (30), a disease that has been attributed to the Th1 response. In adoptive transfer models, using OVA-specific TCR transgenic T cells, both OX40 and 4-1BB costimulatory pathways can influence CD4 and CD8 responses (6,(31)(32)(33).…”
mentioning
confidence: 99%
“…However, bystander activation of CD4 + T cells in addition to virus antigen stimulation may also contribute to HSK development [24]. The continued expression of chemokines including CXCL2, CCL2, CCL3, CCL4, CCL5, and CXCL10 in the cornea would also provide the maintenance of leukocytes in the tissue recruited from the periphery and facilitate collateral damage to the cornea stroma [84]. Collectively, chemokines are instrumental in the initial trafficking of cells into the infected anterior segment of the eye as well as the development of HSK.…”
Section: Adaptive Immune Response To Ocular Hsv-1 Infectionmentioning
confidence: 99%